Resistome and plasmidome in an extensively drug-resistant extra-intestinal pathogenic Escherichia coli isolated from a one-year-old child with respiratory distress syndrome - Van Anh, Nguyen; Thuy Duong, Nguyen; Thanh Tam, Tran Thi; Quang Huy, Nguyen (Vietnam Journal of Biotechnology, 2023)
The global health is facing a growing menace of multidrug-resistant and extensively drug-resistant bacteria over time. Genomic plasticity of pathogenic Escherichia coli allows them to continuously develop and acquire genetic elements associated with antibiotic resistance, including resistance to last resort drugs like carbapenems – only used for the treatment of multidrug-resistant bacterial infections. This study aimed at identifying resistome and plasmidomes carrying antibiotic-resistant genes (ARGs) in an extensively drug-resistant extra-intestinal pathogenic E. coli strain XP817 isolated from a one-year-old child with respiratory distress syndrome. Whole genome analysis of strain XP817 revealed 68 ARGs documented in the Comprehensive Antibiotic Resistance Database (CARD). Notably, strain XP817 possessed 12 ARGs and mutations responsible for its extensively drug-resistant phenotype to aminoglycosides (aacC2 and rmtB), tetracycline (tetA and tetR), bleomycin (bleMBL), chloramphenicol (mdtM), penicillin and cephalosporin (blaCTX-M-27 and blaAmpC), fluoroquinolones (gyrA and parC), macrolide (mphA) and carbapenem (blaNDM-1). Furthermore, five plasmids carrying seven ARGs originated from E. coli strain ECCHD184 (carrying mph(A)) and other species of Enterobacteriaceae family including Enterobacter hormaechei (carrying blaNDM-1 and bleMBL), Proteus mirabilis (carrying tet(A) and tetR), Raoultella ornithinolytica (carrying blaCTX-M-27) and Klebsiella pneumonia (carrying aacC2) were detected. In conclusion, our study underlines the crucial role of the ARG dissemination via horizontal gene transfer in E. coli as well as in the Enterobacteriaceae family.